From Data to Wisdom: A Case Study of OPOP Model - Yikang Sun; Po-Hsien Lin; Rungtai Lin (MDPI AG, 2021)
The purpose of this research is to: (1) clarify the scope and connotation of the OPOP (One Product/Project/Performance, One Paper) model comprehensively; (2) show its application in design and creative teaching; (3) introduce this model to more people. First, the author reviews the design doctoral education system and its shortcomings and analyzes the similarities and differences between "Ph.D. of Design" and "Master of Design"; second, the researcher discusses the DIKW (Data, Information, Knowledge, Wisdom) pyramid, cognition and communication theory separately. The author also interviewed the two teachers who created the OPOP model to clarify its core meaning and goals. Finally, the author invited students who participated in an OPOP forum to fill out a questionnaire in order to analyze and understand their responses and suggestions. The OPOP model allows participants to realize that "creativity" and "interpretation" are equally important and to gradually learn to use academic papers to transform personal "tips" and "experience" into "knowledge" that can be imparted. The author hopes that the OPOP model and the general frameworks mentioned in this study can inspire all readers, enabling them to continuously explore the connotation and further possibilities of OPOP in light of the actual situation.